A reduced chemical kinetic mechanism for computational fluid dynamics simulations of high brake mean effective pressure, lean-burn natural gas engines - Martinez Morett, David, author; Marchese, Anthony J., advisor; Olsen, Daniel B., committee member; Dandy, David S., committee member (Colorado State University. Libraries, 2012)
Recent developments in numerical techniques and computational processing power now permit time-dependent, multi-dimensional computational fluid dynamics (CFD) calculations with detailed chemical kinetic mechanisms using commercially available software. Such computations have the potential to be highly effective tools for designing lean-burn, high brake mean effective pressure (BMEP) natural gas engines that achieve high fuel efficiency and low emissions. Specifically, these CFD simulations can provide the analytical tools required to design highly optimized natural gas engine components such as pistons, intake ports, pre-combustion chambers, fuel systems and ignition systems. To accurately model the transient, multi-dimensional chemically reacting flows present in these systems, detailed chemical kinetic mechanisms are needed that accurately reproduce measured combustion data at high pressures and lean conditions, but are of reduced size to enable reasonable computational times. Prior to the present study, these CFD models could not be used as accurate design tools for application in high BMEP lean-burn gas engines because existing reduced chemical kinetic mechanisms failed to accurately reproduce experimental flame speed and ignition delay data for natural gas at high pressure (40 atm and higher) and lean (0.6 equivalence ratio and lower) conditions. Existing methane oxidation mechanisms had typically been validated with experimental conditions at atmospheric and intermediate pressures (1 to 20 atm) and relatively rich stoichiometry. Accordingly, these kinetic mechanisms were not adequate for CFD simulation of natural gas combustion for which elevated pressures and very lean conditions are typical. This thesis describes an analysis, based on experimental data, of the laminar flame speed computed from numerous, detailed chemical kinetic mechanisms for methane combustion at pressures and equivalence ratios necessary for accurate high BMEP, lean-burn natural gas engine modeling. A reduced mechanism that was shown previously to best match data at moderately lean and high pressure conditions was updated for the conditions of interest by performing sensitivity analysis using CHEMKIN. The reaction rate constants from the most sensitive reactions were appropriately adjusted to obtain better agreement at high pressure lean conditions. An evaluation of two new reduced chemical kinetic mechanisms for methane combustion was performed using Converge CFD software. The results were compared to engine data and a significant improvement on combustion performance prediction was obtained with the new mechanisms.
Keywords: combustion; simulation; natural gas; engine